Prospective Zinc Solubilising Bacteria for Enhanced Nutrient Uptake and Growth Promotion in Maize (Zea mays L.) - Praveen Kumar Goteti; Leo Daniel Amalraj Emmanuel; Suseelendra Desai; Mir Hassan Ahmed Shaik (International Journal of Microbiology)
Zinc (Zn) is one of the essential micronutrients required for optimum plant growth. Substantial quantity of applied inorganic zinc in soil is converted into unavailable form. Zinc solubilising bacteria are potential alternates for zinc supplement. Among 10 strains screened for Zn solubilisation, P29, P33, and B40 produced 22.0 mm clear haloes on solid medium amended with ZnCO3. Similarly, P17 and B40 showed 31.0 mm zone in ZnO incorporated medium. P29 and B40 showed significant release of Zn in broth amended with ZnCO3 (17 and 16.8 ppm) and ZnO (18 and 17 ppm), respectively. The pH of the broth was almost acidic in all the cases ranging from 3.9 to 6.1 in ZnCO3 and from 4.1 to 6.4 in ZnO added medium. Short term pot culture experiment with maize revealed that seed bacterization with P29 @ 10 g·kg−1 significantly enhanced total dry mass (12.96 g) and uptake of N (2.268%), K (2.0%), Mn (60 ppm), and Zn (278.8 ppm).